Histological analysis of the nasal roof cartilage in a neonate sperm whale (Physeter macrocephalus : Mammalia, Odontoceti) - Huggenberger, Stefan; Ridgway, Sam H.; Oelschlager, Helmut H.A.; Kirschenbauer, Irmgard; Vogl, Thomas J.; Klima, Milan (Zoologischer Anzeiger - A Journal of Comparative Zoology, 2006)
The nasal roof cartilage of a neonate sperm whale (Physeter macrocephalus) was examined by gross dissection and routine histology. This cartilage is part of the embryonic Tectum nasi and is a critical feature in the formation of the massive sperm whale forehead. In neonates as well as in adults, the blade-like nasal roof cartilage extends diagonally through the huge nasal complex from the bony nares to the blowhole on the left side of the rostral apex of the head. It accompanies the left nasal passage along its entire length, which may reach several meters in adult males. The tissue of the nasal roof cartilage in the neonate whale shows an intermediate state of development. For example, in embryos and fetuses, the nasal roof cartilage consists of hyaline cartilage, but in adult sperm whales, it also includes elastic fibers. In our neonate sperm whale, the nasal roof cartilage already consisted of adult-like elastic cartilage. In addition, the active or growing, layer of the perichondrium was relatively thick compared to that of fetuses, and a large number of straight, elastic fibers that were arranged perpendicularly to the long axis of the nasal roof cartilage were present. These neonatal features call be interpreted as characteristics of immature and growing cartilaginous tissue. An important function of the nasal roof cartilage may be the stabilization of the left nasal passage, which is embedded within the soft tissue of the nasal complex. The nasal roof cartilage with its elastic fibers may keep the nasal passage open and prevent its collapse from Bernoulli forces during inhalation. Additionally, the intrinsic tension of the massive nasal musculature may be a source of compression on the nasal roof cartilage and could explain its hyaline character in the adult. In our neonate specimen, in contrast, the cartilaginous rostrum (i.e., mesorostral cartilage) consisted of hyaline cartilage with an ample blood supply. The cartilaginous rostrum does not change its histological characteristics during development, ...